Age-related (aged vs. adult) comparison of the effect of two mild stressors on the nerve growth factor (NGF) in the rat hypothalamic supraoptic nucleus (SON) - immunohistochemical study - Badowska-Szalewska, E; Ludkiewicz, B; Krawczyk, R; Moryś, J (Folia biologica (Praha), 2016)
The ontogenetic period of life and stress can have different effects on the nerve growth factor (NGF) in the hypothalamus. The aim of our study was to investigate the influence of two mild stressors, acute and chronic exposure to forced swim (FS) or high-light open field (HL-OF), on neurons containing NGF. Immunofluorescence staining was used to reveal the density of NGF-immunoreactive (ir) cells in the hypothalamic supraoptic nucleus (SON) in adult (postnatal day 90; P90) and aged (P720) rats. The P90 and P720 rats that were subjected to acute and chronic FS showed no differences in the density of NGF-ir neurons in the SON compared with nonstressed rats. However, a significant increase in NGF-ir cells was noted after acute but not after chronic HL-OF only in P90 rats. What is more, there were no age-related (P90 vs. P720) changes in the density of NGF-ir neurons in non-stressed and FS- or HL-OF-stressed rats. Our results indicate that acute HL-OF was the only factor inducing changes in the density of NGF-ir neurons in the SON of adult rats. This could be related to the neuroprotective role of NGF-ir cells in response to acute HL-OF. The absence of age-dependent changes in the density of NGF-ir neurons may indicate that the ageing processes in SON do not generate changes in the NGF immunoreactivity of its neurons.
Keywords: Swimming; nucleus supraopticus; nervový růstový faktor; Nerve Growth Factor; stárnutí; počet buněk; zvířata; Supraoptic Nucleus; Immunohistochemistry; neurony; Aging; imunohistochemie; potkani Wistar; Stress, Psychological; Rats, Wistar; Male; Neurons; psychický stres; Animals; mužské pohlaví; plavání; Cell Count